Advances of metaheuristic algorithms in training neural networks for industrial applications - Chong H.Y.; Yap H.J.; Tan S.C.; Yap K.S.; Wong S.Y. (Springer Science and Business Media Deutschland GmbH, 2023)
Backpropagation; Gradient methods; Neural networks; Artificial neural network models; Complex applications; Exploration and exploitation; Gradient-based learning; Industry applications; Meta heuristic algorithm; Meta-heuristic search algorithms; Near-optimal solutions; Optimization